THE REPRESENTATIONS OF THE CLAIMED INDONESIAN CULTURAL HERITAGE ISSUEIN THE JAKARTA POST AND ANTARA NEWSA SYSTEMIC FUNCTIONAL GRAMMAR ANALYSIS - Evi Karlina Ambarwati, - (2009)
This research paper presents a Functional Grammar analysis of the representations of the claimed Indonesian Cultural Heritage issue in two English newspapers in Indonesia, namely, The Jakarta Post and ANTARA News. Representation refers to the use of language to say something or represent the world meaningfully to other people (Hall 1997). Analysis of the three strands of meaning in Hallidayan Functional Grammar-ideational, interpersonal and textual meaning- by the system of transitivity, Mood and thematic structure was applied to the articles of the two newspapers. Textually, it was found that The Jakarta Post and ANTARA News favored discussing topics about Indonesia. It was proved by the high frequency of Indonesia as unmarked themes (35.05% and 58.82% in The Jakarta Post and ANTARA News respectively) compared to other topics, such as Malaysia or the issue. However, they had different emphasis on the discussion about Indonesia. The Jakarta Post represents Indonesia as "the victim" who "suffers", "is embarrassing", "bad", "upwind" and "aghast". Meanwhile, Malaysia is "the active perpetrator" who "used" and "patented" some pieces of Indonesian cultural heritage. Contrary, ANTARA News represents Indonesia in a "neutral" position with no negative or positive adjective was given to it. Malaysia was represented "to have claimed" Indonesian cultural heritage. The two newspapers tended to be implicit in rendering their views. They used different strategies in implicitly deliver their points of interest. The Jakarta Post used median value of modality (52.63%) and hypothetical clauses as well as Conjunctions in the clauses (65.30%). In addition, The Jakarta Post favored the Relational Process (35.24%) as an attempt to implicitly hide the actors and actions involved in the clauses. Meanwhile, ANTARA News used a low level of modality (66.66%) and WH-relatives (78.57%).